2020
DOI: 10.2147/ott.s235882
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Sequential Infusion of Anti-CD22 and Anti-CD19 Chimeric Antigen Receptor T Cells for a Pediatric Ph-Like B-ALL Patient That Relapsed After CART-Cell and Haplo-HSCT Therapy: A Case Report and Review of Literature</p>

Abstract: Pediatric Philadelphia chromosome-like (Ph-like) acute B-lymphoblastic leukemia (B-ALL), a high-risk subset of BALL characterized by a gene expression profile similar to that of Ph-positive ALL, has extremely poor outcome after a relapse following autologous chimeric antigen receptor (CAR)-T and haploidentical (haplo) hematopoietic stem cell transplantation(HSCT)therapy. with very limited treatment options. Donor-derived CAR T-cell therapy, the most vital advanced anticancer technology, may be a promising salv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…At present, dual-target infusion is considered as a promising and effective strategy for the antigen-loss relapse after single-target CAR-T cells ( 32 ). A previous meeting abstract and a case report showed that sequential infusions could significantly improve the clinical outcome of r/r B-ALL patients as well ( 33 , 34 ). Recently, sequential infusion of two single-specific CAR-T cells was proposed as a cocktail therapy in r/r B-ALL patients for its proved superior efficacy and safety in the clinical trial ( 35 ), while thus far, few clinical trials comparing the efficacy of dual-target and sequential infusions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…At present, dual-target infusion is considered as a promising and effective strategy for the antigen-loss relapse after single-target CAR-T cells ( 32 ). A previous meeting abstract and a case report showed that sequential infusions could significantly improve the clinical outcome of r/r B-ALL patients as well ( 33 , 34 ). Recently, sequential infusion of two single-specific CAR-T cells was proposed as a cocktail therapy in r/r B-ALL patients for its proved superior efficacy and safety in the clinical trial ( 35 ), while thus far, few clinical trials comparing the efficacy of dual-target and sequential infusions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mini-TCR iPS-T cells offer many specific advantages, such as accepting newly developed CAR constructs including co-expression of memory T cell-related cytokines such as interleukin (IL)-15 14 , 53 and dual-targeting CAR approaches. 54 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the treatment of pediatric R/R B-ALL by orderly infusing CD19 and CD22 CAR-T cells can prevent antigen escape and prolong the duration of remission. 88 In a phase I clinical trial of CD19/CD22 dual-target CAR-T cells to treat B-ALL in China, all 6 patients obtained MRD-negative CR, and none of them developed central toxicity. 89 Coincidentally, in another clinical trial of patients with R/R invasive B-cell lymphoma treated with CD19/CD22 dual-target CAR-T cells, of the 16 eligible patients, 14 (87.5%) achieved an objective response, and 10 (62.5%) got achieved a CR.…”
Section: Antigen-negative Relapsementioning
confidence: 99%